2014
DOI: 10.1002/ajmg.a.36478
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking, xenobiotic metabolizing enzyme gene variants, and gastroschisis risk

Abstract: Maternal smoking during pregnancy is one proposed risk factor for gastroschisis, but reported associations have been modest, suggesting that differences in genetic susceptibility might play a role. We included 108 non-Hispanic white and 62 Hispanic families who had infants with gastroschisis, and 1147 non-Hispanic white and 337 Hispanic families who had liveborn infants with no major structural birth defects (controls) in these analyses. DNA was extracted from buccal cells collected from infants and mothers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 43 publications
2
32
1
Order By: Relevance
“…Gastroschisis requires surgical repair at birth and is associated with significant bowel related morbidity (e.g., intestinal atresia and short bowel syndrome) [Lepigeon et al, 2014]. Obese women [Khodr et al, 2013;Jenkins et al, 2014] and mothers of black race/ethnicity [Vu et al, 2008;Kirby et al, 2013] have repeatedly been shown to be at decreased risk of having fetuses with gastroschisis. Obese women [Khodr et al, 2013;Jenkins et al, 2014] and mothers of black race/ethnicity [Vu et al, 2008;Kirby et al, 2013] have repeatedly been shown to be at decreased risk of having fetuses with gastroschisis.…”
Section: Introductionmentioning
confidence: 99%
“…Gastroschisis requires surgical repair at birth and is associated with significant bowel related morbidity (e.g., intestinal atresia and short bowel syndrome) [Lepigeon et al, 2014]. Obese women [Khodr et al, 2013;Jenkins et al, 2014] and mothers of black race/ethnicity [Vu et al, 2008;Kirby et al, 2013] have repeatedly been shown to be at decreased risk of having fetuses with gastroschisis. Obese women [Khodr et al, 2013;Jenkins et al, 2014] and mothers of black race/ethnicity [Vu et al, 2008;Kirby et al, 2013] have repeatedly been shown to be at decreased risk of having fetuses with gastroschisis.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have examined the interaction between smoking and gene variants for their combined risk of gastroschisis and cleft palate [Jenkins and others 2014; Torfs and others 2006; Wu and others 2012]. …”
Section: Discussionmentioning
confidence: 99%
“…The few studies that do exist examined the interaction with smoking [Jenkins and others 2014; Torfs and others 2006; Wu and others 2012] or nutrition [Enaw and others 2006; Wu and others 2010] and one with occupational chemical exposures [Shaw and others 2003]. Fewer such gene-environment interaction studies have been conducted specifically on spina bifida with most focused on folate transport or metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…One mother who provided samples for herself reported using an egg donor, and her data were removed from analyses of sample collectors. Selected exposures and birth defects were chosen based on their use in NBDPS gene-environment interaction studies, sample sizes, and previous reported associations (Cleves, Hobbs, Zhao, Krakowiak, & MacLeod, 2011; Correa et al, 2008; Hackshaw, Rodeck, & Boniface, 2011; Hobbs et al, 2014; Jenkins et al, 2014; Lupo et al, 2012; Tang, Cleves et al, 2015; Tang, Hobbs et al, 2015). We considered the associations between three exposures and six phenotypes to assess whether sample collection participation impacts the observed associations over a range of sample sizes.…”
Section: Methodsmentioning
confidence: 99%